Comprehensive insight into the food safety climate in Central and Eastern Europe. (August 2020) - Tomasevic, Igor; Kovačević, Danijela Bursać; Jambrak, Anet Režek; Zsolt, Szendrő; Dalle Zotte, Antonella; Martinović, Aleksandra; Prodanov, Mirko; Sołowiej, Bartosz; Sirbu, Alexandrina; Subić, Jonel; Roljević, Svetlana; Semenova, Anastasia; et al.
Abstract: This investigation provides an important insight into the Central and Eastern European food industry, beyond traditional food safety management and reflects on its food safety (FS) climate or the human route of its FS culture. Investigation was conducted in 10 Central and Eastern European countries involving more than 500 food companies. Overall FS climate was assessed as good. The availability of infrastructure was perceived the same in all countries although "resources" was the lowest scored climate component. Uncertainty avoiding national cultures had a stronger preference towards written FS procedures and instructions. FS climate was better assessed in bigger companies because small companies observed weaker availability of resources, smaller number of procedures and instructions and reduced risk awareness. FS communication and commitment were not affected by company size. The share of food companies without FS system was five times higher in small compared to big companies. No effect of FS management level or riskiness level on FS climate scores was apparent. Food companies seemed to avoid problems in cooperation and trust between FS leaders and other employees, since they have perceived FS climate similarly. The strongest FS climate segmentation in Central and Eastern Europe food companies was observed in terms of the EU membership status. EU operating food companies managed to develop a very good and distinctive FS climate, with better-perceived leadership, communication, commitment, resources and risk awareness than non-EU food companies. Transitional economic environment of non-EU countries have undesirably influenced the organisational and technological support in their companies and employees perceptions of FS climate. Highlights: 10 countries and 503 food companies surveyed. Overall food safety climate very good. Better food safety climate in larger companies. No influence of national culture on food safety climate. EU companies had better climate than non-EU companies.